Under-reporting of Risky Drug Use Among Primary Care Patients in Federally Qualified Health Centers. Issue 6 (November 2016) - Bone, Curtis; Gelberg, Lilian; Vahidi, Mani; Leake, Barbara; Yacenda-Murphy, Julia; Andersen, Ronald M.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The Affordable Care Act encourages integration of behavioral health into primary care. We aim to estimate the level of under-reporting of drug use in federally qualified health centers (FQHCs) among self-reported risky drug users. Methods: Adult patients in the waiting rooms of 4 FQHCs who self-reported risky drug use on the screening instrument World Health Organization's Alcohol, Smoking and Substance Involvement Screening Test (score 4–26), who participated in the "Quit Using Drugs Intervention Trial, " submitted urine samples for drug testing. Under-reporters were defined as patients who denied use of a specific drug via questionnaire, but whose urine drug test was positive for that drug. Descriptive statistics, Pearson chi-square test, and logistic regression were used for analysis. Results: Of the 192 eligible participants, 189 (96%) provided urine samples. Fifty-four samples were negative or indeterminate, yielding 135 participants with positive urine drug tests for this analysis: 6 tested positive for amphetamines, 18 opiates, 21 cocaine, 97 marijuana. Thirty patients (22%) under-reported drug use and 105 (78%) reported drug use accurately. Under-reporting by specific substances was: amphetamines 66%, opiates 45%, cocaine 14%, and marijuana 7%. Logistic regression revealed that under-reporting of any drug was associated with history of incarceration and older age (odds ratios 2.6 and 3.3, respectively; P < 0.05). Conclusions: Under-reporting of drug use is prevalent even among self-reported drug users in primary care patients of FQHCs (22%), but varied considerably based on the substance used. Further research is indicated to assess the extent of under-reporting among all primary care patients, regardless of their self-reported drug use status.